Mathematical modeling of the thermal degradation kinetics of vitamin C in cupuaçu (Theobroma grandiflorum) nectar - Vieira, Margarida C. (2011)
The thermal degradation kinetics of both components of vitamin C, ascorbic acid (AA) and dehydroascorbic acid (DHAA), were determined in a nectar of Cupuacßu (Theobroma grandi¯orum) with 25% of pulp and 15% of sugar in water. AA was assayed by HPLC and the results showed that AA degraded into DHAA. A reversible ®rst order model described well the AA degradation data, with an activation energy of 74 5 kJ/mol and k80 C 0:032 0:003min ÿ1. DHAA kinetic behavior suggested a consecutive ®rst order reaction where DHAA was the intermediate product of AA degradation. A mechanistic model was derived to predict DHAA concentration. Rate constants were replaced by the Arrhenius equation in the model to evaluate the temperature dependence and the kinetic parameters for AA degradation, previously determined, were used. An activation energy of 65 9 kJ/mol and a k80 C of 0:013 0:003 min ÿ1 were estimated. The present ®ndings will help to predict the best Cupuacßu nectar processing conditions that minimize degradation of an important quality factor such as vitamin C.